2017
DOI: 10.1242/jcs.197848
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of pericyte α6β1-integrin in tumour blood vessels

Abstract: The α6β1-integrin is a major laminin receptor, and formation of a laminin-rich basement membrane is a key feature in tumour blood vessel stabilisation and pericyte recruitment, processes that are important in the growth and maturation of tumour blood vessels. However, the role of pericyte α6β1-integrin in angiogenesis is largely unknown. We developed mice where the α6-integrin subunit is deleted in pericytes and examined tumour angiogenesis and growth. These mice had: (1) reduced pericyte coverage of tumour bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
0
26
1
Order By: Relevance
“…Consistent with these data, integrin‐α1∼α3 and ‐α6 are found in cultured CNS pericytes at mRNA level (Stratman et al ., ). At protein level, expression of integrin‐α2 (Yao et al ., ), ‐α6 (Reynolds et al ., ), and ‐β1 (Abraham et al ., ; Turlo et al ., ) in pericytes/SMCs has been reported. In addition, there is also evidence showing that pericytes synthesize integrin‐α7 (Flintoff‐Dye et al ., ; Silva et al ., ).…”
Section: Expression Of Laminins and Their Receptors In The Cnsmentioning
confidence: 99%
“…Consistent with these data, integrin‐α1∼α3 and ‐α6 are found in cultured CNS pericytes at mRNA level (Stratman et al ., ). At protein level, expression of integrin‐α2 (Yao et al ., ), ‐α6 (Reynolds et al ., ), and ‐β1 (Abraham et al ., ; Turlo et al ., ) in pericytes/SMCs has been reported. In addition, there is also evidence showing that pericytes synthesize integrin‐α7 (Flintoff‐Dye et al ., ; Silva et al ., ).…”
Section: Expression Of Laminins and Their Receptors In The Cnsmentioning
confidence: 99%
“…During development, pericytes are first attracted to newly formed capillaries via the endothelial-secreted chemoattractant platelet-derived growth factor (PDGF)-BB, which binds to PDGF receptor β (PDGFRβ) on pericytes (Lindahl et al, 1997;Benjamin et al, 1998). Integrin-mediated adhesion of pericytes to laminin helps to maintain expression of PDGFRβ (Durbeej, 2010;Reynolds et al, 2017). Interference with PDGF-BB/PDGFRβ signaling is sufficient to disrupt endothelial-pericyte interactions (Lindahl et al, 1997), indicating that perpetual signaling through PDGFRβ is critical to maintain pericyte localization to capillary endothelial cells.…”
Section: Introduction: What Is a Pericyte?mentioning
confidence: 99%
“…Integrins are known to regulate cell-cell and cell-matrix interactions and it has amply been reported that integrins may be involved in tumor progression and metastasis [39][40][41]. According to the "seed-and-soil" hypothesis, metastatic organotropism is one of the characteristics of cancer [42].…”
Section: Discussionmentioning
confidence: 99%